New Genera of Neotropical Therevidae (Insecta: Diptera) - Webb, Donald W. (Zootaxa, 2005)
Five new Neotropical genera of Stiletto flies, Amplisegmentum Webb, Apenniverpa Webb, Ptilotophallos Webb, Spiracolis Webb, and Winthemmyia Webb are described. Each genus and associated species are described with illustrations of their genitalia and distribution information. Their placement within the subfamily Therevinae is discussed.